Reduced Expression of TMEM16A Impairs Nitric Oxide-Dependent Cl− Transport in Retinal Amacrine Cells - Rodriguez, Tyler Christopher; Zhong, Li; Simpson, Hailey; Gleason, Evanna (Frontiers in Cellular Neuroscience, 2022)
Postsynaptic cytosolic Cl- concentration determines whether GABAergic and glycinergic synapses are inhibitory or excitatory. We have shown that nitric oxide (NO) initiates release of Cl- from acidic internal stores into the cytosol of retinal amacrine cells (ACs) thereby elevating cytosolic Cl-. In addition, we found that cystic fibrosis transmembrane conductance regulator (CFTR) expression as well as Ca2+ elevations are necessary for the transient effects of NO on cytosolic Cl- levels but the mechanism remains to be elucidated. Here, we investigate the involvement of TMEM16A as a link between Ca2+ elevations and cytosolic Cl- release. TMEM16A is a Ca2+ -activated Cl- channel that is functionally coupled with CFTR in epithelia. Both proteins are also expressed in neurons. Based on this, and its Ca2+ dependence, we test the hypothesis that TMEM16A participates in the NO-dependent elevation in cytosolic Cl- in ACs. Chick retina ACs express TMEM16A by western blot analysis, single cell PCR, and immunocytochemistry. Electrophysiology experiments demonstrate TMEM16A functions in amacrine cells. Pharmacological inhibition of TMEM16A with T16inh-AO1 reduces the NO-dependent Cl- release as indicated by the diminished shift in the reversal potential of GABAA receptor-mediated currents. We confirmed the involvement of TMEM16A in the NO-dependent Cl- release using CRISPR/Cas9 knockdown of TMEM16A. Two different modalities targeting the gene for TMEM16A (ANO1) were tested in retinal amacrine cells: an all-in-one plasmid vector and crRNA/tracrRNA/Cas9 ribonucleoprotein. The all-in-one CRISPR/Cas9 modality did not change the expression of TMEM16A protein and produced no change in the response to NO. However, TMEM16A-specific crRNA/tracrRNA/Cas9 ribonucleoprotein effectively reduces both TMEM16A protein levels and the NO-dependent shift in reversal potential of GABA-gated currents. These results show that TMEM16A plays a role in the NO-dependent Cl- release from retinal ACs.